Triple Flexion Reflex - Ryoya Yamaguchi; Junki Mizumoto; Akira Ohya (Annals of Internal Medicine: Clinical Cases)
We present here a clinical video demonstrating a triple flexion reflex caused by a plasma cell tumor infiltrating the spinal canal. This involuntary movement is a characteristic and rare manifestation that occurs in association with spinal cord compression and can be observed without motor weakness. Therefore, the clinician should carefully examine the spine even if the patient has little or no muscle depression.